The Overview of the Conservation and Renewal of the Industrial Belgian Heritage as a Vector for Cultural Regeneration - Jiazhen Zhang; Jeremy Cenci; Vincent Becue; Sesil Koutra (Information, 2021)
Industrial heritage reflects the development track of human production activities and witnessed the rise and fall of industrial civilization. As one of the earliest countries in the world to start the Industrial Revolution, Belgium has a rich industrial history. Over the past years, a set of industrial heritage renewal projects have emerged in Belgium in the process of urban regeneration. In this paper, we introduce the basic contents of the related terms of industrial heritage, examine the overall situation of protection and renewal in Belgium. The industrial heritage in Belgium shows its regional characteristics, each region has its representative industrial heritage types. In the Walloon region, it is the heavy industry. In Flanders, it is the textile industry. In Brussels, it is the service industry. The kinds of industrial heritages in Belgium are coordinate with each other. Industrial heritage tourism is developed, especially on eco-tourism, experience tourism. The industrial heritage in transportation and mining are the representative industrial heritages in Belgium. There are a set of numbers industrial heritages are still in running based on a successful reconstruction into industrial tourism projects. Due to the advanced experience in dealing with industrial heritage, the industrial heritage and the city live together harmoniously.